COVID-19-Related Intracerebral Hemorrhage - Pavlov, Valentin; Beylerli, Ozal; Gareev, Ilgiz; Torres Solis, Luis Fernando; Solís Herrera, Arturo; Aliev, Gjumrakch (Frontiers in Aging Neuroscience, 2020)
Intracerebral hemorrhage (ICH) is a common and severe neurological disorder and is associated with high rates of mortality and morbidity. ICH is associated with old age and underlying conditions such as hypertension and diabetes mellitus. The COVID-19 pandemic is associated with neurological symptoms and complications including ICH. For instance, the mechanisms by which COVID-19 may contribute to hemorrhagic stroke may include both depletion of angiotensin converting enzyme 2 (ACE2) receptor and overactive immune response. In this study, we herein report three patients (0.25%) out of 1200 admissions with COVID-19 to our center between 1 May and August 4, 2020, who developed ICH. In addition, we will briefly discuss the possible pathophysiological mechanisms of COVID-19 infection in patients with ICH.